Lessons from the Field Beyond the Numbers: Narratives of Professionals on Women who Experienced Severe Maternal Morbidity - Carina Fernanda Robles Angelini; Rodolfo de Carvalho Pacagnella; Carla Silveira; Carla Betina Andreucci; Elton Carlos Ferreira; Juliana Pereira Santos; Dulce Maria Toledo Zanardi; Mary Angela Parpinelli; Maria Laura Costa; José Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective Several factors might affect the health and the quality of life of women who had a severe maternal morbidity (SMM) or a maternal near-miss (MNM) episode. The objective of the present study was to explore the perspectives of the professionals on the repercussions of SMM or of MNM after interviewing women who survived such episodes. Method Selected cases that captured the attention of professionals were reported. The professionals built individually 10 narratives, which were analyzed with the technique of content analysis. Results According to the perspectives of the professionals, women surviving a severe maternal condition and their families experienced clinical and psychosocial consequences. Some cases portrayed the intense psychological distress in mourning for the loss of the fetus or of their reproductive capacity and changes in family dynamics generating emotional overload, depression, and gender violence. Conclusion The analysis of narratives may offer an idea on the complexity of the perception of care by professionals and on the need for an interdisciplinary follow-up of women surviving an SMM or an MNM episode.